Efeito dos íons Fe3+ na estrutura de perovskitas à base de titânio obtidas via método hidrotérmico de micro-ondas - Peixoto, Diego Alves (2021)
In this work, pure, 2.0 and 4.0 mol% of Fe3+ doped nanostructures of barium titanate (BaTiO3) and strontium titanate (SrTiO3) perovskites were synthesized by hydrothermal microwave assisted method. The materials were obtained at 140 ºC with a heating rate of 5 ºC min-1 for 8 min. The X-ray diffraction results indicated the formation of the tetragonal structure for the BaTiO3 and cubic for the SrTiO3. The presence of Fe3+ caused long-range disturbances at the crystalline grid of the materials due to substitution of Ti4+ and Fe3+. The Raman active modes that characterize the tetragonal structure of BaTiO3 and the cubic structure of SrTiO3 were observed. Raman spectra also revealed local distortions generated by the addition of Fe3+ in the structures of these materials. UV-vis spectra revealed low intensity d-d transition bands of the Fe3+ due to the low concentration of these ions in the titanates lattice. From these spectra it was possible to calculate the band gap energy values for the samples. The values obtained were relatively lower for the doped samples. The images of scanning electron microscopy by field emission indicated the doping ion influence on the morphology of the formed particles. The BaTiO3 samples were made up of small and agglomerated particles and the doped samples with Fe3+ showed larger particles with rounded morphology. The SrTiO3 samples showed cube-shaped particles ranging in size from 200 to 600 nm. The doped samples had smaller particles than the pure SrTiO3 sample. The spectra obtained by energy dispersive X-ray spectroscopy (EDX) confirmed the presence of iron element in the doped samples. The insertion of Fe3+ promoted a decrease in the intensity of photoluminescent emission compared to the pure samples suggesting that the presence of dopant decreased the electron recombination in the titanates structures.